2013
DOI: 10.3140/bull.geosci.1454
|View full text |Cite
|
Sign up to set email alerts
|

Amphiperatherium and Erinaceidae of Petersbuch 28

Abstract: The only marsupial and the Erinaceidae from the Bavarian fissure filling Petersbuch 28 are described. The marsupial is Amphiperatherium frequens erkertshofense, the Erinaceidae are represented by Galerix aurelianensis and an unknown large galericine, which is present only by four isolated teeth. The three species are mostly present by single teeth; distal ends of humeri of Amphiperatherium and Galerix, astragali of Galerix as well as calcanei of Amphiperatherium are also described; the calcaneus for the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…The small marsupial Amphiperatherium is quite common in contemporary faunas from southern Germany (Ziegler and Fahlbusch 1986;Klietmann et al 2014a). Marsupials have also been found in faunas from the CalatayudMontalbán Basin (L. van den Hoek Ostende, personal observation), but unfortunately, the material was lost.…”
Section: Family Soricidae Fischer 1814mentioning
confidence: 99%
“…The small marsupial Amphiperatherium is quite common in contemporary faunas from southern Germany (Ziegler and Fahlbusch 1986;Klietmann et al 2014a). Marsupials have also been found in faunas from the CalatayudMontalbán Basin (L. van den Hoek Ostende, personal observation), but unfortunately, the material was lost.…”
Section: Family Soricidae Fischer 1814mentioning
confidence: 99%
“…The latest research reported on only one piece of P4 and an M1 with a broken outer edge (Figs. 2.3-2.4) (Klietmann et al, 2014). After our comparison, we discovered that the hypocone in P4 of Oligoechinus was located behind the protocone and was close to the tongue side and that a weak crista connected the protocone and hypocone.…”
Section: Comparison and Discussionmentioning
confidence: 77%
“…The known species from the Oligocene include Palaeoscaptor, Metexallerix and Amphechinus (Huang, 1984;Qiu and Gu, 1988;Wang et al, 1981;Daxner-Höck et al, 2017), whereas species from European and American areas that have similar characters include those belonging to the Galericinea, Apulogalerix, Galerix and Parasorex (Fig. 2) (Mein and Suárez, 1993;Ziegler, 2005;Furió et al, 2010;Federico and Flaviano, 2013;Klietmann et al, 2014;Prieto et al, 2015).…”
Section: Comparison and Discussionmentioning
confidence: 99%
“…Occurrences-Amphiperatherium frequens in early Miocene localities in Germany and France (Von Koenigswald, 1970;Crochet, 1980;Ziegler, 1990b;Klietmann et al, 2014).…”
Section: Systematic Paleontologymentioning
confidence: 99%